Effectiveness of E-Advertisement on Customer’s Online Purchase Intention in Saudi - Al-dheleai, Mohammed Najib Saleh Mohammed; Yeni, Yulia Hendri; Syafrizal, Syafrizal (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2024)
With the end goal to make customers happy, it is of incredible significance for the organizations to comprehend online customers’ purchasing conduct and explore the factors that influence the customer’s online purchase intention. The fundamental purpose behind why online purchase intention is of such significance for firms is on the grounds that it is a solid indicator of real online purchase. Therefore, it is important to conduct research on online purchase intention to gain a richer comprehension about internet business and customers' online purchase intention. However, in spite of the fact that the development is huge in internet shopping in Saudi Arabia, logical comprehension of the customers’ online purchase intention in Saudi Arabia is inadequate. Thus, it is essential for e-retailers to comprehend the elements that may impact the choice of the customers in shopping on the web. This study tries to fill this current research gap by observationally discovering what factors are essential for them that influence in purchasing on the web in the setting of Saudi Arabia. The targeted sample for this study is the customers’ who prefer online purchase in Saudi Arabia. The research distributed the questionnaire through online and obtained a total of 106 responses which were found valid for further analysis. This study employed multiple regression for data analysis and hypotheses testing. The results indicate that attitude towards design, information quality, influence of social networking, and perceived risk significantly influence online purchase intention among Saudi Arabian online consumers. Finally, the implications are discussed and future recommendations are proposed.